Pengaruh Pengembangan Karir dan Pelatihan Kerja terhadap Komitmen Kerja Karyawan pada PT. Maybank Finance Pekanbaru - Kurnia Prantara; Seno Andri (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
This research aims to determine the effect of career development and job training on employee work commitment at PT Maybank Finance Pekanbaru. This research uses descriptive and quantitative statistical methods using a Likert scale as measurement. The population used is Maybank Finance consumers. The sample for this research consisted of 35 respondents who were determined using saturated sampling techniques and using questionnaires in data collection techniques. The analysis of this research includes instrument tests, classical assumption tests and statistical tests which are processed using tools in the form of SPSS version 25. The results of this research show that career development partially has a significant effect on employee work commitment, partial work training has a significant effect on employee work commitment. Career development and job training simultaneously have a significant effect on employee work commitment.